MoOx-Nafion composite film as well as preparation method and application thereof

By uniformly filling MoO3 nanosheets or MoO2 nanoparticles in the Nafion film, the swelling-filling method is used to solve the problem of mechanical performance degradation when improving the proton conductivity, and the high proton conductivity and stability are achieved.

CN119170841APending Publication Date: 2024-12-20GUANGXI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411326778.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the process of improving the proton conductivity, the mechanical performance degradation and uneven distribution of the filling material lead to damage to the overall performance, and the adverse effects caused by inappropriate preparation methods.

Method used

MoOx-Nafion composite membrane was used to soak the Nafion membrane by immersing the MoO3 nanosheets or MoO2 nanoparticle suspension solution, and heat and drying in H2SO4 solution and water. The modifications were uniformly filled with the "swell-filled" method to protect the complete structure of the Nafion membrane. sex.

Benefits of technology

The proton conductivity of the Nafion membrane is significantly improved, while maintaining other key properties, avoiding the decline in mechanical properties, and ensuring the stability and overall performance of the composite membrane are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170841A_ABST
    Figure CN119170841A_ABST
Patent Text Reader

Abstract

The invention provides a MoOx-Nafion composite film as well as a preparation method and application thereof. According to the MoOx-Nafion composite membrane disclosed by the invention, the Nafion membrane is uniformly filled with MoOx, and MoOx has high stability and rich oxygen atoms on the surface, so that MoOx can be used as an adsorption site of water molecules and a potential jump transmission site of protons, and the proton conductivity of the Nafion membrane is remarkably improved; the composite membrane is prepared by adopting a'swelling-filling 'method, the Nafion membrane is soaked in a filling modifier solution, Nafion is swelled, a skeleton structure is'expanded', and the Nafion membrane is uniformly filled with the filling modifier under the action of concentration gradient, so that the integrity of the original structure of the Nafion membrane is effectively protected, and the influence on other properties of the membrane material is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of proton exchange membranes, in particular to a MoO x -Nafion composite membrane and its preparation method and application. Background Art

[0002] As a highly efficient energy conversion device, the proton exchange membrane fuel cell (PEMFC) can safely convert hydrogen energy into electrical energy and is the best choice for hydrogen energy utilization. As the core component of the fuel cell system, the proton exchange membrane (PEM) plays the role of transferring protons and isolating the anode and cathode. Its comprehensive performance will directly affect the performance of the entire system. At present, the PEM material with the most extensive commercial application is the Nafion membrane produced by DuPont. The Nafion membrane has excellent overall performance, but there is still a lot of room for improvement in some specific performance aspects, such as proton conductivity and mechanical stability.

[0003] There are many studies on improving the proton conductivity of Nafion membranes, among which the use of inorganic fillers and Nafion to prepare composite membranes is one of the common modification methods. Such inorganic fillers as modifiers usually need to have good stability and have the ability to conduct protons or assist proton conduction. The proton conductivity performance of modified composite membranes can usually be significantly improved, but there are still some problems that limit the application of such composite membranes. On the one hand, due to the characteristics of the functional groups on the surface of the modified materials or the compatibility with the matrix, the mechanical properties of the composite membranes are reduced; on the other hand, due to the inappropriate selection of the modification preparation method, the filling modified materials are unevenly distributed, which has an adverse effect on the overall performance of the composite membrane.

[0004] Based on the defects of the current preparation of composite membranes using Nafion, it is necessary to improve it. Summary of the invention

[0005] In view of this, the present invention provides a MoO x -Nafion composite membrane and its preparation method and application, MoO x -Nafion composite membrane has high proton conductivity and effectively avoids affecting other key properties of membrane materials.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a MoO x -Nafion composite membrane, comprising a Nafion membrane and MoO doped in the Nafion membrane x , the MoO x Including MoO3 nanosheets or MoO2 nanoparticles.

[0008] In a second aspect, the present invention also provides a MoO x -A method for preparing a Nafion composite membrane comprises the following steps:

[0009] The MoO3 nanosheets or MoO2 nanoparticles are respectively prepared into a MoO3 nanosheet suspension solution or a MoO2 nanoparticle suspension solution;

[0010] The Nafion membrane is immersed in a MoO3 nanosheet suspension solution or a MoO2 nanoparticle suspension solution to obtain an immersed Nafion membrane;

[0011] The soaked Nafion membrane was placed in H2SO4 solution and water in turn, heated and dried to obtain MoO x -Nafion composite membrane.

[0012] Preferably, in the step of soaking the Nafion membrane in the MoO3 nanosheet suspension solution or the MoO2 nanoparticle suspension solution, the soaking temperature is 20-25°C and the soaking time is 1-4 hours.

[0013] Preferably, the soaked Nafion membrane is placed in a H2SO4 solution with a concentration of 0.5 to 1 mol / L and treated at 80 to 90°C for 1 to 2 hours;

[0014] Then, the Nafion membrane treated with H2SO4 was placed in water and treated at 80-90℃ for 1-2h, and dried to obtain MoO x -Nafion composite membrane.

[0015] Preferably, the Nafion membrane is pretreated before being immersed in the MoO3 nanosheet suspension solution or the MoO2 nanoparticle suspension solution, and the pretreatment specifically includes: placing the Nafion membrane in a hydrogen peroxide solution with a mass concentration of 3-4% at 90-100°C for 1-2 hours, washing with water, then placing the Nafion membrane in a H2SO4 solution with a concentration of 0.5-1 mol / L, at 90-100°C for 1-2 hours, then placing the Nafion membrane in water, at 90-100°C for 1-2 hours, and then washing with water;

[0016] And / or, before placing the soaked Nafion membrane in H2SO4 solution and water in sequence, the method further includes: washing the soaked Nafion membrane with water and then drying it.

[0017] Preferably, the preparation method of the MoO3 nanosheet suspension solution is:

[0018] (NH4)6Mo7O 24Dissolve in water, add HCl to acidify, heat and stir, then centrifuge, wash and dry to obtain MoO3 powder;

[0019] The MoO3 powder is calcined to obtain MoO3 nanosheets;

[0020] Adding MoO3 nanosheets to an ethanol aqueous solution, ultrasonicating, and taking the supernatant to obtain a MoO3 nanosheet suspension solution;

[0021] The preparation method of the MoO2 nanoparticle suspension solution is:

[0022] MoO3 powder is added to a mixed solution of water and ethylene glycol, heated for reaction, and then centrifuged, washed, and dried to obtain MoO2 nanoparticles;

[0023] MoO2 nanoparticles were added into ethanol aqueous solution, ultrasonicated, and the supernatant was taken to obtain a MoO2 nanoparticle suspension solution.

[0024] Preferably, (NH4)6Mo7O 24 Dissolve in water, add HCl to pH 1-1.5, stir at 80-90℃ for 2-4h, centrifuge, wash and dry to obtain MoO3 powder; (NH4)6Mo7O 24 The mass volume ratio with water is (4-6) g: (50-60) mL;

[0025] The MoO3 powder is calcined at 400-500°C for 2-4h to obtain MoO3 nanosheets;

[0026] In the step of adding MoO3 nanosheets to the ethanol aqueous solution, the volume ratio of ethanol to water in the ethanol aqueous solution is (1-3):(1-3), and the mass volume ratio of MoO3 powder to the ethanol aqueous solution is (0.25-0.30) g:(50-60) mL.

[0027] Preferably, MoO3 powder is added to a mixed solution of water and ethylene glycol, reacted at 180-190°C for 2-3 hours, and then centrifuged, washed, and dried to obtain MoO2 nanoparticles.

[0028] Preferably, in the step of adding MoO3 powder to a mixed solution of water and ethylene glycol, the volume ratio of water to ethylene glycol is (7-10):(3-5), and the mass volume ratio of the mixed solution of MoO3 powder, water and ethylene glycol is (0.4-0.5) g:(60-70) mL;

[0029] In the step of adding MoO2 nanoparticles to the ethanol aqueous solution, the volume ratio of ethanol to water in the ethanol aqueous solution is (1-3):(1-3), and the mass volume ratio of MoO2 nanoparticles to the ethanol aqueous solution is (0.2-0.3) g:(50-60) mL.

[0030] In the third aspect, the present invention also provides a MoO x -Nafion composite membrane or the MoO prepared by the preparation method x -Application of Nafion composite membrane as proton exchange membrane in fuel cells.

[0031] A MoO of the present invention x -Nafion composite membrane and its preparation method and application have the following beneficial effects compared with the prior art:

[0032] 1. MoO of the present invention x -Nafion composite membrane, MoO x Uniformly filled in Nafion membrane, due to MoO x It has high stability and abundant oxygen atoms on the surface, which can serve as adsorption sites for water molecules and potential jump transmission sites for protons, significantly improving the proton conductivity of Nafion membranes.

[0033] 2. MoO of the present invention x -Nafion composite membrane preparation method, adopts "swelling-filling" method to prepare composite membrane, immerses Nafion membrane in filling modifier (namely MoO3 nanosheet or MoO2 nanoparticle) solution, Nafion swells, skeleton structure is "opened", under the action of concentration gradient, filling modifier is evenly filled into Nafion membrane, which effectively protects the integrity of original structure of Nafion membrane and avoids affecting other properties of membrane material. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 The present invention is a flow chart of the preparation method of the MoO2 nanoparticle suspension solution and the MoO3 nanosheet suspension solution;

[0036] Figure 2The SEM image (b) of the MoO3 nanosheets prepared in Example 1 and the TEM image (a) of the MoO2 nanoparticles prepared in Example 2;

[0037] Figure 3 The XRD patterns of the MoO3 nanosheets prepared in Example 1 and the MoO2 nanoparticles prepared in Example 2;

[0038] Figure 4 The SEM image and EDS element distribution map of the Nafion-MoO2-3h composite membrane prepared in Example 2;

[0039] Figure 5 XRD pattern of pure Nafion membrane (Pristine Nafion) used for comparison of Nafion-MoO2-3h membrane and Nafion-MoO3-2h membrane prepared in Example 2;

[0040] Figure 6 It is a comparison chart of dry film thickness (Dry Thickness), water uptake (Water Uptake) and volume swelling rate (Volume Swelling) of Nafion-MoO3-1h, Nafion-MoO3-2h, Nafion-MoO3-3h prepared in Example 1, Nafion-MoO2-2h, Nafion-MoO2-3h, Nafion-MoO2-4h prepared in Example 2 and pure Nafion membrane;

[0041] Figure 7 is the proton conductivity of the Nafion-MoO2-2h, Nafion-MoO2-3h, Nafion-MoO2-4h composite membranes and pure Nafion membrane prepared in Example 2 at 100% RH and 30-80°C;

[0042] Figure 8 is the proton conductivity of the Nafion-MoO3-1h, Nafion-MoO3-2h, Nafion-MoO3-3h composite membranes and pure Nafion membrane prepared in Example 1 at 100% RH and 30-80°C;

[0043] Fig. 9 Thermal gravimetric curves of Nafion-MoO3-1h, Nafion-MoO3-2h, Nafion-MoO3-3h composite membranes prepared in Example 1, Nafion-MoO2-2h, Nafion-MoO2-3h, Nafion-MoO2-4h composite membranes prepared in Example 2, and pure Nafion membrane;

[0044] Fig.10(a) is the content of MoO2 in the Nafion-MoO2-2h, Nafion-MoO2-3h and Nafion-MoO2-4h composite membranes prepared in Example 2; Fig.10 (b) is the content of MoO3 in the Nafion-MoO3-1h, Nafion-MoO3-2h and Nafion-MoO3-3h composite membranes prepared in Example 1.

[0045] Fig.11 The stress-strain curves are those of the Nafion-MoO3-1h, Nafion-MoO3-2h, Nafion-MoO3-3h composite membranes prepared in Example 1, the Nafion-MoO2-2h, Nafion-MoO2-3h, Nafion-MoO2-4h composite membranes prepared in Example 2, and the pure Nafion membrane;

[0046] Fig.12 This is the test curve of hydrogen-oxygen single cell composed of the Nafion-MoO3-2h composite membrane prepared in Example 1, the Nafion-MoO2-2h composite membrane prepared in Example 2 and a pure Nafion membrane (test conditions 60°C, 100% RH). DETAILED DESCRIPTION

[0047] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0048] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.

[0050] The present application embodiment provides a MoO x -Nafion composite membrane, including Nafion membrane and MoO doped in Nafion membrane x ,MoO x Including MoO3 nanosheets or MoO2 nanoparticles.

[0051] MoO of the present invention x -Nafion composite membrane, MoO x Uniformly filled in Nafion membrane, due to MoO x It has high stability and abundant oxygen atoms on its surface, which can serve as adsorption sites for water molecules and potential hopping transmission sites for protons, significantly improving the proton conductivity of Nafion membranes.

[0052] Specifically, Nafion membrane is Nafion diaphragm, and its foreign name is nafionnr 50 (beads 10-35mesh), which is a perfluorosulfonic acid diaphragm.

[0053] Based on the same inventive concept, the present invention also provides a MoO x -A method for preparing a Nafion composite membrane comprises the following steps:

[0054] S1, preparing MoO3 nanosheets or MoO2 nanoparticles into a MoO3 nanosheet suspension solution or a MoO2 nanoparticle suspension solution respectively;

[0055] S2, soaking the Nafion membrane in a MoO3 nanosheet suspension solution or a MoO2 nanoparticle suspension solution to obtain an immersed Nafion membrane;

[0056] S3, placing the soaked Nafion membrane in H2SO4 solution and water in turn, heating and drying to obtain MoO x -Nafion composite membrane.

[0057] In the above embodiment, MoO x -Nafion composite membrane preparation method, comprising: soaking the Nafion membrane in a MoO3 nanosheet suspension solution, or soaking the Nafion membrane in a MoO2 nanoparticle suspension solution to obtain a soaked Nafion membrane; then placing the soaked Nafion membrane in H2SO4 solution and water in turn, removing impurities, and drying to obtain MoO x -Nafion composite membrane.

[0058] In some embodiments, in the step of soaking the Nafion membrane in a MoO3 nanosheet suspension solution or a MoO2 nanoparticle suspension solution, the soaking temperature is 20 to 25°C and the soaking time is 1 to 4 hours.

[0059] In some embodiments, the soaked Nafion membrane is placed in a H2SO4 solution with a concentration of 0.5 to 1 mol / L and treated at 80 to 90° C. for 1 to 2 hours;

[0060] Then, the Nafion membrane treated with H2SO4 was placed in water and treated at 80-90℃ for 1-2h, and dried to obtain MoO x -Nafion composite membrane.

[0061] In some embodiments, the Nafion membrane is pretreated before being immersed in a MoO3 nanosheet suspension solution or a MoO2 nanoparticle suspension solution, respectively. The pretreatment specifically includes: placing the Nafion membrane in a hydrogen peroxide solution with a mass concentration of 3 to 4% at 90 to 100°C for 1 to 2 hours, washing with water, and then placing the Nafion membrane in a H2SO4 solution with a concentration of 0.5 to 1 mol / L, and treating it at 90 to 100°C for 1 to 2 hours, and then placing the Nafion membrane in water, treating it at 90 to 100°C for 1 to 2 hours, and then washing with water.

[0062] In some embodiments, before placing the soaked Nafion membrane in H2SO4 solution and water in sequence, the method further includes: washing the soaked Nafion membrane with water and then drying it.

[0063] In some embodiments, the preparation method of the MoO3 nanosheet suspension solution is:

[0064] S11, (NH4)6Mo7O 24As a precursor, it is dissolved in water, acidified by adding HCl, heated and stirred, and then centrifuged, washed, and dried to obtain MoO3 powder;

[0065] S12, calcining the MoO3 powder to obtain MoO3 nanosheets;

[0066] S13, adding MoO3 nanosheets to an ethanol aqueous solution, ultrasonicating, taking the supernatant, and obtaining a MoO3 nanosheet suspension solution;

[0067] In some embodiments, the preparation method of the MoO2 nanoparticle suspension solution is:

[0068] S21, adding MoO3 powder to a mixed solution of water and ethylene glycol, heating for reaction, and then centrifuging, washing, and drying to obtain MoO2 nanoparticles;

[0069] S22. Add MoO2 nanoparticles to ethanol aqueous solution, perform ultrasound treatment, and take the supernatant to obtain a MoO2 nanoparticle suspension solution.

[0070] In some embodiments, (NH4)6Mo7O 24 Dissolve in water, add HCl to pH 1-1.5, stir at 80-90℃ for 2-4h to generate molybdic acid precipitate, centrifuge, wash and dry to obtain MoO3 powder; (NH4)6Mo7O 24 The mass volume ratio with water is (4-6) g: (50-60) mL;

[0071] The MoO3 powder is calcined at 400-500°C for 2-4h to obtain MoO3 nanosheets;

[0072] In the step of adding MoO3 nanosheets to the ethanol aqueous solution, the volume ratio of ethanol to water in the ethanol aqueous solution is (1-3):(1-3), and the mass volume ratio of MoO3 powder to the ethanol aqueous solution is (0.25-0.30) g:(50-60) mL.

[0073] In some embodiments, MoO3 powder is added to a mixed solution of water and ethylene glycol, reacted at 180-190°C for 2-3 hours, and then centrifuged, washed, and dried to obtain MoO2 nanoparticles.

[0074] In some embodiments, in the step of adding MoO3 powder to a mixed solution of water and ethylene glycol, the volume ratio of water to ethylene glycol is (7-10):(3-5), and the mass volume ratio of the mixed solution of MoO3 powder, water and ethylene glycol is (0.4-0.5) g:(60-70) mL;

[0075] In the step of adding MoO2 nanoparticles to the ethanol aqueous solution, the volume ratio of ethanol to water in the ethanol aqueous solution is (1-3):(1-3), and the mass volume ratio of MoO2 nanoparticles to the ethanol aqueous solution is (0.2-0.3) g:(50-60) mL.

[0076] refer to Figure 1 As shown, it shows the preparation method of the MoO2 nanoparticle suspension solution and the MoO3 nanosheet suspension solution of the present invention; specifically, (NH4)6Mo7O 24 ·4H2O was dissolved in water, and after adding HCl to acidify, it was stirred at 80℃ for 2h, and then centrifuged and washed to remove impurities to obtain white MoO3 powder; the MoO3 powder was calcined at 400℃ for 2h to obtain gray-white MoO3 nanosheets; the MoO3 nanosheets were added to an ethanol aqueous solution (the volume ratio of ethanol to water was 1:1), ultrasonicated, and the supernatant was taken to obtain a MoO3 nanosheet suspension solution; the MoO3 powder was added to a mixed solution containing 42mL deionized water and 18mL ethylene glycol, and reacted at 180℃ in a reactor for 2h, the precipitate was collected and dried to obtain MoO2 nanoparticles; the MoO2 nanoparticles were added to an ethanol aqueous solution (the volume ratio of ethanol to water was 1:1), ultrasonicated, and the supernatant was taken to obtain a MoO2 nanoparticle suspension solution.

[0077] The prior art discloses the preparation of composite membranes by casting, pouring or spraying, which requires that the Nafion membrane (semifluorosulfonic acid resin or polymer resin) be first dissolved in an organic solvent and then mixed with a modifier, which will cause the original ordered nano phase separation structure of the Nafion membrane to be destroyed, resulting in certain properties of the composite membrane being affected, such as mechanical properties. In order to avoid the above-mentioned effects, the present invention adopts the "swelling-filling" method to prepare the composite membrane. The Nafion membrane is immersed in a solution of a filling modifier (i.e., MoO3 nanosheets or MoO2 nanoparticles), the Nafion swells, the skeleton structure is "opened", and the filling modifier is uniformly filled into the Nafion membrane under the action of a concentration gradient. This effectively protects the integrity of the original structure of the Nafion membrane and avoids affecting other key properties of the membrane material.

[0078] Based on the same inventive concept, the present invention also provides a MoO x -Nafion composite membrane or the above-mentioned preparation method to prepare MoO x -Application of Nafion composite membrane as proton exchange membrane in fuel cells.

[0079] The following further describes the MoO of the present application with specific examples. x-Nafion composite membrane and its preparation method and application. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0080] In the following examples, the Nafion membrane is a commercially available product, specifically Dupont, model Nafion 212.

[0081] Example 1

[0082] The present application embodiment provides a MoO x -Nafion composite membrane preparation method, such as Figure 1 As shown, the following steps are included:

[0083] S1, 5.0g (NH4)6Mo7O 24 4H2O was dissolved in 50mL water, HCl was added until the pH was 1, and the mixture was stirred at 80℃ for 2h, then centrifuged and washed to remove impurities. The washed precipitate was fully dried at 80℃ to remove moisture, and then ground to obtain white MoO3 powder;

[0084] S2, 0.288 g of MoO3 powder was calcined at 400 °C for 2 h to obtain off-white MoO3 nanosheets;

[0085] S3, adding MoO3 nanosheets to 50 mL of ethanol aqueous solution (the volume ratio of ethanol to water is 1:1), ultrasonicating for 12 h, centrifuging at 5000 r / min for 4 min, taking the supernatant, and obtaining a MoO3 nanosheet suspension solution;

[0086] S4, pre-treating the Nafion membrane; the pre-treatment specifically includes: placing the Nafion membrane in a 3% hydrogen peroxide solution at 95°C for 1 hour, washing with deionized water, then placing the Nafion membrane in a 0.5 mol / L H2SO4 solution at 95°C for 1 hour, then placing the Nafion membrane in water at 95°C for 1 hour, and then soaking it in deionized water for standby use;

[0087] S5, soaking the pretreated Nafion membrane in a MoO3 nanosheet suspension solution (immersion time is 1h, 2h, 3h respectively), taking it out and rinsing it with deionized water, drying it, and obtaining an immersed Nafion membrane; the immersion temperature is 25°C;

[0088] S6, placing the soaked Nafion membrane in a 0.5 mol / L H2SO4 solution at 80°C for 1 h;

[0089] The Nafion membrane treated with H2SO4 was placed in deionized water and treated at 80℃ for 1h and dried to obtain MoO x -Nafion composite membrane; wherein the MoO prepared by immersion time of 1h, 2h, and 3h x -Nafion composite membranes were recorded as Nafion-MoO3-1h, Nafion-MoO3-2h, and Nafion-MoO3-3h, respectively.

[0090] Example 2

[0091] The present application embodiment provides a MoO x -Nafion composite membrane preparation method, such as Figure 1 As shown, the following steps are included:

[0092] S1, 5.0g (NH4)6Mo7O 24 4H2O was dissolved in 50mL water, HCl was added until the pH was 1, and the mixture was stirred at 80℃ for 2h, then centrifuged and washed to remove impurities. The washed precipitate was fully dried at 80℃ to remove moisture, and then ground to obtain white MoO3 powder;

[0093] S2, adding 0.432g MoO3 powder to a mixed solution containing 42mL deionized water and 18mL ethylene glycol, stirring for 10min, then transferring to a reactor, reacting at 180°C for 2h, cooling to room temperature, centrifuging to obtain a dark brown precipitate, washing with ethanol and deionized water, collecting the precipitate, and drying to obtain MoO2 nanoparticles;

[0094] S3, adding 0.256 g of MoO2 nanoparticles to 50 mL of ethanol aqueous solution (the volume ratio of ethanol to water is 1:1), ultrasonicating for 12 h, centrifuging at 5000 r / min for 4 min, taking the supernatant to obtain a MoO2 nanoparticle suspension solution;

[0095] S4, pre-treating the Nafion membrane; the pre-treatment specifically includes: placing the Nafion membrane in a 3% hydrogen peroxide solution at 95°C for 1 hour, washing with deionized water, then placing the Nafion membrane in a 0.5 mol / L H2SO4 solution at 95°C for 1 hour, then placing the Nafion membrane in water at 95°C for 1 hour, and then soaking it in deionized water for standby use;

[0096] S5, soaking the pretreated Nafion membrane in a MoO2 nanoparticle suspension solution (immersion time is 2h, 3h, 4h respectively), taking it out and rinsing it with deionized water, drying it, and obtaining an immersed Nafion membrane; the immersion temperature is 25°C;

[0097] S6, placing the soaked Nafion membrane in a 0.5 mol / L H2SO4 solution at 80°C for 1 h;

[0098] The Nafion membrane treated with H2SO4 was placed in deionized water and treated at 80℃ for 1h and dried to obtain MoO x -Nafion composite membrane; wherein the MoO prepared by immersion time of 2h, 3h, and 4h x -Nafion composite membranes were recorded as Nafion-MoO2-2h, Nafion-MoO2-3h, and Nafion-MoO2-4h, respectively.

[0099] Performance Characterization

[0100] like Figure 2 As shown, the morphology of molybdenum oxide can be characterized by TEM and SEM tests. Figure 2 (a) is a TEM image of the MoO2 nanoparticles prepared in Example 2. It can be seen from the figure that the size of the prepared MoO2 particles is between 20 and 30 nm. Figure 2 (b) is a SEM image of the MoO3 nanosheets prepared in Example 1. It can be seen from the figure that the prepared MoO3 has a distinct flaky structure with uneven sizes. The thickness of the nanosheets is about 100 nm, which is significantly larger than the MoO2 nanoparticles.

[0101] like Figure 3 As shown in the figure, from the XRD spectrum of MoO2 nanoparticles, it can be seen that three strong diffraction peaks appear at 25.96°, 36.72° and 53.38°, corresponding to the ((110)(011)), (262) and (022) crystal planes of MoO2 (PDF#78-1073), respectively, confirming the successful synthesis of MoO2 nanoparticles. The XRD spectrum of MoO3 nanosheets shows five characteristic peaks at 2θ of 12.76°, 23.33°, 25.70°, 27.34° and 38.98°, corresponding to the (020), (110), (040), (021) and (060) crystal planes of MoO3 (PDF#05-0508), respectively. The remaining diffraction peaks are basically consistent with the standard card of MoO3 (PDF#78-1073), which can be considered that the crystal phase of the synthesized MoO3 nanosheets is relatively pure.

[0102] Figure 4The SEM image and EDS element distribution diagram of the Nafion-MoO2-3h composite membrane prepared in Example 2.

[0103] like Figure 4 As shown in Figure 1, the cross-section of the Nafion-MoO2-3h composite membrane was characterized by SEM, and elemental analysis was performed by EDS. It can be seen from the figure that the cross-section of the composite membrane is relatively flat, without obvious cracks and particles, and the Mo element distribution diagram shows that MoO2 is successfully filled into the Nafion membrane and maintains a uniform distribution.

[0104] Figure 5 XRD pattern of pure Nafion membrane (Pristine Nafion) used for comparison of Nafion-MoO2-3h membrane and Nafion-MoO3-2h membrane prepared in Example 2.

[0105] like Figure 5 As shown, through XRD analysis of the composite membrane and pure Nafion membrane, it was further confirmed that the microstructure of the composite membrane did not undergo significant damage. Compared with the pure Nafion membrane, the XRD spectrum of the composite membrane did not change significantly. This is mainly because the filling amount of MoO2 and MoO3 in the composite membrane is relatively small and evenly distributed, so there are no obvious characteristic peaks belonging to MoO2 and MoO3. This shows that the use of the "swelling-filling" strategy to prepare the composite membrane can make MoO2 and MoO3 evenly distributed in the Nafion membrane matrix and well retain the original microstructure of the Nafion membrane, which will certainly be beneficial to the improvement of the overall performance of the composite membrane.

[0106] Figure 6 This is a comparison chart of the dry film thickness (Dry Thickness), water absorption (Water Uptake) and volume swelling rate (Volume Swelling) of Nafion-MoO3-1h, Nafion-MoO3-2h, Nafion-MoO3-3h prepared in Example 1, Nafion-MoO2-2h, Nafion-MoO2-3h, Nafion-MoO2-4h prepared in Example 2 and pure Nafion membrane.

[0107] Specifically, the water uptake and swelling rate of the membrane samples were determined by the difference in weight and size under wet and dry conditions. All samples were dried in an oven at 60°C for 24 hours before testing, and the mass in the dry state (W d ), length (L d )、Width(T d ) and thickness (D d), then, the sample was immersed in deionized water at room temperature for 24 h, the extra liquid on the membrane surface was removed and the wet weight of the sample (W) was quickly recorded. w ), length (L w )、Width(T w ) and thickness (D w ). The calculation formula is as follows:

[0108] Water absorption:

[0109] Swelling rate:

[0110] like Figure 6 As shown, MoO x -Nafion composite membrane dry film thickness does not change much, indicating that the filling of MoO3 nanosheets and MoO2 nanoparticles did not cause significant damage to the original molecular structure of the Nafion membrane, retaining its structural integrity. The water absorption rate of the composite membrane is significantly improved compared with the pure Nafion membrane, among which the water absorption rate of Nafion-MoO2-2h and Nafion-MoO3-1h membranes is increased by 30% and 38% respectively compared with the pure Nafion membrane. This is mainly due to the rich oxygen atom active sites on the surface of MoO2 and MoO3, which can form rich hydrogen bonds and enhance the water absorption of the membrane, which will help improve the proton conduction performance of the proton exchange membrane. In addition, the volume swelling rate of the composite membrane modified by MoO2 nanoparticle filling is lower than that of the pure Nafion membrane, indicating that when MoO2 nanoparticles are used as fillers, the dimensional stability of the composite membrane is enhanced. The volume swelling rate of the composite membrane using MoO3 nanosheets as filler is slightly higher than that of the original membrane, and with the increase of treatment time, the water absorption rate decreases, and the volume swelling first increases and then decreases. This is because the MoO3 nanosheets have more oxygen atoms on the surface and better water absorption, which to a certain extent causes excessive swelling of the composite membrane and affects the dimensional stability of the composite membrane. In addition, MoO3 nanosheets have a large size and cross-sectional area. With the increase of filling time and the increase of filling amount, MoO3 nanosheets will occupy a large amount of space and block the proton transmission channels in the membrane, thereby affecting the water absorption and stability of the membrane.

[0111] Figure 7 It is the proton conductivity of the Nafion-MoO2-2h, Nafion-MoO2-3h, Nafion-MoO2-4h composite membranes and pure Nafion membrane prepared in Example 2 under the conditions of 100% RH and 30-80°C.

[0112] Figure 8It is the proton conductivity of the Nafion-MoO3-1h, Nafion-MoO3-2h, Nafion-MoO3-3h composite membranes and pure Nafion membrane prepared in Example 1 under the conditions of 100% RH and 30-80°C.

[0113] like Figures 7-8 As shown in the figure, under 100% RH conditions, in the range of 30-80℃, the conductivity of Nafion-MoO2 membrane and Nafion-MoO3 membrane with different treatment time is improved compared with pure Nafion membrane within the experimental test range, which is consistent with the water absorption test results. Among them, the proton conductivity of Nafion-MoO2-3h composite membrane and Nafion-MoO3-2h composite membrane under 30℃ full humidity conditions is relatively high, which is 0.130S / cm and 0.135S / cm, respectively, which is 26% and 31% higher than that of pure Nafion membrane. This is mainly due to the rich hydrogen bonding between the oxygen atoms on the surface of MoO2 nanoparticles and MoO3 nanosheets and the sulfonic acid groups in the membrane, which promotes the conduction of protons in the membrane. In addition, it can be seen from Figures 7-8 that with the increase of treatment time, the conductivity of Nafion-MoO2 membrane first increases and then stabilizes, while the conductivity of Nafion-MoO3 membrane first increases and then decreases. This is because the appropriate amount of filling MoO x The water absorption of the membrane can be enhanced and the conductivity of the membrane can be improved, but overfilling will affect the connectivity of the proton transport channels in the membrane, thereby affecting proton transfer. In particular, the volume of MoO3 nanosheets is large, and their sheet structure is more likely to hinder the activity of water molecules and protons when overfilled.

[0114] Fig. 9 Thermal gravimetric loss curves of Nafion-MoO3-1h, Nafion-MoO3-2h, Nafion-MoO3-3h composite membranes prepared in Example 1, Nafion-MoO2-2h, Nafion-MoO2-3h, Nafion-MoO2-4h composite membranes prepared in Example 2, and pure Nafion membrane.

[0115] like Fig. 9 As shown in Figure 3, the thermal gravimetric curve of the composite membrane is basically consistent with that of the pure Nafion membrane, which indicates that the filling modification does not have a negative impact on the overall thermal stability of the composite membrane.

[0116] Fig.10 (a) is the content of MoO2 in the Nafion-MoO2-2h, Nafion-MoO2-3h and Nafion-MoO2-4h composite membranes prepared in Example 2; Fig.10(b) is the mass content of MoO3 in the Nafion-MoO3-1h, Nafion-MoO3-2h and Nafion-MoO3-3h composite membranes prepared in Example 1.

[0117] like Fig.10 As shown, according to the residual mass of the composite film in the thermogravimetric curve, the content of MoO2 and MoO3 in the composite film is calculated, which can explain that MoO2 and MoO3 are successfully filled into the Nafion film, and as the composite film filling treatment time increases, the filling amount of MoO2 and MoO3 in the film increases significantly. In addition, combined with the proton conductivity test results of the composite film, it can be seen that when the content of MoO2 in the Nafion-MoO2 composite film is about 1% (i.e., Nafion-MoO2-3h film), it shows good proton conductivity under low temperature and full humidity conditions, and when the content of MoO3 in the Nafion-MoO3 composite film is 0.7% (i.e., Nafion-MoO3-2h film), it shows good proton conductivity under low temperature and full humidity conditions. Therefore, introducing an appropriate amount of MoO2 and MoO3 into the Nafion film can greatly improve the proton conductivity of the composite film.

[0118] Fig.11 These are the stress-strain curves of the Nafion-MoO3-1h, Nafion-MoO3-2h, Nafion-MoO3-3h composite membranes prepared in Example 1, the Nafion-MoO2-2h, Nafion-MoO2-3h, Nafion-MoO2-4h composite membranes prepared in Example 2, and the pure Nafion membrane.

[0119] like Fig.11As shown in the figure, the mechanical stability of Nafion-MoO2-2h membrane in Nafion-MoO2 composite membrane is good, its maximum tensile stress is 21.24MPa, and its elongation at break is 244%, which is 22% higher than that of pure Nafion membrane. The Nafion-MoO3-2h membrane in Nafion-MoO3 composite membrane has good stability, its maximum tensile stress is 21.55MPa, and its elongation at break is 228%, which is 14% higher than that of pure Nafion membrane. By comparison, it is found that with the increase of filling treatment time, the maximum tensile stress and elongation at break of the composite membrane decrease, indicating that the mechanical stability is weakened. In summary, the appropriate filling treatment time can improve the mechanical properties of molybdenum oxide / Nafion composite membrane to a certain extent. The abundant active oxygen atoms on the surface of MoO2 and MoO3 can form a large number of hydrogen bonds with sulfonic acid groups, thereby improving the mechanical properties of the composite membrane. When the filling time is too long, the molybdenum oxide filling amount is too much, which may cause certain damage to the unique cluster structure in the Nafion membrane, which has an adverse effect on the overall mechanical properties of the composite membrane.

[0120] Fig.12 The single cell test curve of proton exchange membrane hydrogen and oxygen composed of Nafion-MoO3-2h composite membrane prepared in Example 1, Nafion-MoO2-2h composite membrane prepared in Example 2 and pure Nafion membrane (test conditions 60°C, 100% RH). The single cell test of proton exchange membrane was carried out on the MiniTest3000 Fuel Cell Test System (TOYO Corporation) test platform. Commercial Pt / C catalyst was sprayed on both sides of the membrane and covered with carbon paper, and then installed in the battery fixture. The Pt / C loading in the Pt / C catalyst is 0.2 mg / cm 2 , the flow rates of hydrogen and oxygen were 0.2 L / min and 0.5 L / min, respectively.

[0121] like Fig.12 As shown in the figure, considering the comprehensive performance of molybdenum oxide-Nafion composite membrane, Nafion-MoO2-3h membrane and Nafion-MoO3-2h membrane were finally selected for hydrogen-oxygen single cell test. Under full humidity conditions at 60℃, the maximum power density of Nafion-MoO2-3h composite membrane can reach 746mW / cm 2 , which is about 25% higher than that of pure Nafion membrane. The maximum power density of Nafion-MoO3-2h composite membrane can reach 736mW / cm 2, which is about 23% higher than that of pure Nafion membrane. The polarization curves in the comparison graph show that the polarization curve of Nafion-MoO3-2h composite membrane becomes steeper in the final current region, indicating that the internal impedance of the fuel cell increases, which will directly affect the improvement of the proton conduction efficiency of the membrane material. The above results show that the use of a lossless swelling filling strategy to fill molybdenum oxide into the Nafion membrane can improve the comprehensive performance of the membrane, among which MoO2 nanoparticles have a better modification effect on the Nafion membrane.

[0122] The oxidation stability and proton conductivity of the Nafion-MoO3-1h, Nafion-MoO3-2h, Nafion-MoO3-3h composite membranes prepared in Example 1, the Nafion-MoO2-2h, Nafion-MoO2-3h, Nafion-MoO2-4h composite membranes prepared in Example 2 and the pure Nafion membrane (Pristine Nafion) were tested, and the results are shown in Table 1 below.

[0123] Table 1 - Oxidative stability and proton conductivity of composite membranes prepared in different embodiments

[0124]

[0125] The oxidation stability test method in Table 1 is: the residual mass percentage after the membrane material is immersed in Fenton solution (a H2O2 solution with a mass concentration of 3% and containing 3 ppm FeSO4) for 1 hour and 24 hours; the proton conductivity test method is: the membrane material is tested for its conductivity under 80°C and 100% RH conditions.

[0126] As shown in Table 1, compared with pure Nafion membrane, the Nafion-MoO2 composite membrane and Nafion-MoO3 composite membrane after "swelling-filling" modification still showed higher residual mass after immersion for 1h and 24h, and after immersion for 24h, the composite membrane still showed higher proton conductivity than the pure Nafion membrane, which indicates that MoO2 nanoparticles and MoO3 nanosheets have a positive effect on enhancing the oxidative stability of the composite membrane.

[0127] In summary, the MoO provided by the present invention x -Nafion composite membrane, compared with pure Nafion membrane, MoO x -Nafion composite membrane proton conductivity has been significantly improved, this is due to the rich hydrogen bonding between the oxygen atoms on the surface of molybdenum oxide and the sulfonic acid groups in the membrane, which promotes the conduction of protons in the membrane. At the same time, the mechanical and chemical stability of the composite membrane has been enhanced to a certain extent, which will further improve the comprehensive performance of the composite membrane.

[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A MoO x -Nafion composite membrane, characterized in that A Nafion membrane and MoO doped in the Nafion membrane x , the MoO x Including MoO3 nanosheets or MoO2 nanoparticles.

2. A MoO as claimed in claim 1 x -A method for preparing a Nafion composite membrane, characterized in that: The following steps are involved: The MoO3 nanosheets or MoO2 nanoparticles are respectively prepared into a MoO3 nanosheet suspension solution or a MoO2 nanoparticle suspension solution; The Nafion membrane is immersed in a MoO3 nanosheet suspension solution or a MoO2 nanoparticle suspension solution to obtain an immersed Nafion membrane; The soaked Nafion membrane was placed in H2SO4 solution and water in turn, heated and dried to obtain MoO x -Nafion composite membrane.

3. MoO according to claim 2 x -A method for preparing a Nafion composite membrane, characterized in that: In the step of soaking the Nafion membrane in the MoO3 nanosheet suspension solution or the MoO2 nanoparticle suspension solution, the soaking temperature is 20-25°C and the soaking time is 1-4 hours.

4. MoO according to claim 2 x -A method for preparing a Nafion composite membrane, characterized in that: The soaked Nafion membrane is placed in a H2SO4 solution with a concentration of 0.5-1 mol / L and treated at 80-90°C for 1-2 hours; Then, the Nafion membrane treated with H2SO4 was placed in water and treated at 80-90℃ for 1-2h, and dried to obtain MoO x -Nafion composite membrane.

5. MoO according to claim 2 x -A method for preparing a Nafion composite membrane, characterized in that: Before the Nafion membrane is immersed in the MoO3 nanosheet suspension solution or the MoO2 nanoparticle suspension solution, the Nafion membrane is pretreated. The pretreatment specifically includes: placing the Nafion membrane in a hydrogen peroxide solution with a mass concentration of 3-4% at 90-100°C for 1-2 hours, washing with water, then placing the Nafion membrane in a H2SO4 solution with a concentration of 0.5-1 mol / L, at 90-100°C for 1-2 hours, then placing the Nafion membrane in water, at 90-100°C for 1-2 hours, and then washing with water; And / or, before placing the soaked Nafion membrane in H2SO4 solution and water in sequence, the method further includes: washing the soaked Nafion membrane with water and then drying it.

6. MoO according to claim 2 x -A method for preparing a Nafion composite membrane, characterized in that: The preparation method of the MoO3 nanosheet suspension solution is: (NH4)6Mo7O 24 Dissolve in water, add HCl to acidify, heat and stir, then centrifuge, wash and dry to obtain MoO3 powder; The MoO3 powder is calcined to obtain MoO3 nanosheets; Adding MoO3 nanosheets to an ethanol aqueous solution, ultrasonicating, and taking the supernatant to obtain a MoO3 nanosheet suspension solution; The preparation method of the MoO2 nanoparticle suspension solution is: MoO3 powder is added to a mixed solution of water and ethylene glycol, heated for reaction, and then centrifuged, washed, and dried to obtain MoO2 nanoparticles; The MoO2 nanoparticles were added into an ethanol aqueous solution, ultrasonicated, and the supernatant was taken to obtain a MoO2 nanoparticle suspension solution.

7. MoO according to claim 6 x -A method for preparing a Nafion composite membrane, characterized in that: (NH4)6Mo7O 24 Dissolve in water, add HCl to pH 1-1.5, stir at 80-90℃ for 2-4h, centrifuge, wash and dry to obtain MoO3 powder; (NH4)6Mo7O 24 The mass volume ratio with water is (4-6) g: (50-60) mL; The MoO3 powder is calcined at 400-500°C for 2-4h to obtain MoO3 nanosheets; In the step of adding MoO3 nanosheets to the ethanol aqueous solution, the volume ratio of ethanol to water in the ethanol aqueous solution is (1-3):(1-3), and the mass volume ratio of MoO3 powder to the ethanol aqueous solution is (0.25-0.30) g:(50-60) mL.

8. MoO according to claim 6 x -A method for preparing a Nafion composite membrane, characterized in that: MoO3 powder is added to a mixed solution of water and ethylene glycol, reacted at 180-190°C for 2-3 hours, and then centrifuged, washed and dried to obtain MoO2 nanoparticles.

9. MoO according to claim 6 x -A method for preparing a Nafion composite membrane, characterized in that: In the step of adding MoO3 powder to a mixed solution of water and ethylene glycol, the volume ratio of water to ethylene glycol is (7-10):(3-5), and the mass volume ratio of the mixed solution of MoO3 powder, water and ethylene glycol is (0.4-0.5) g:(60-70) mL; In the step of adding MoO2 nanoparticles to the ethanol aqueous solution, the volume ratio of ethanol to water in the ethanol aqueous solution is (1-3):(1-3), and the mass volume ratio of MoO2 nanoparticles to the ethanol aqueous solution is (0.2-0.3) g:(50-60) mL.

10. MoO according to claim 1 x -Nafion composite membrane or MoO prepared by the preparation method described in any one of claims 2 to 9 x -Application of Nafion composite membrane as proton exchange membrane in fuel cells.